Development of a Gluten Standard from Relevant Sources of Wheat and Investigation into Gluten Content of Supplemental Enzymes Generated During Fermentation - Pyeongsug Kim; Natasha Kim Leeuwendaal; Jonathon Niño Charari; Joan Colom; John Deaton; Kieran Rea (Fermentation)
During fermentation, bacterial and fungal species synthesize substrate-specific enzymes to obtain nutrients. During this process, potential allergenic products, including immunologically important gluten peptides, can be created. Current protocols for assessing the levels of these peptides often overlook the specific gluten source. In this study, wheat sources provided by commercial enzyme suppliers underwent gluten extraction before being pooled into a Complete Gluten Mix, which then underwent variations of hydrolysis utilizing the digestive enzymes, pepsin and trypsin complexes. The resulting gluten peptide profiles were examined using the Wes automated Western blot system to confirm the presence of small, immunologically relevant gluten peptides. These hydrolysates were further tested for suitability as a relevant calibrant against commercially available ELISA standards. The PT3 calibrant, a hydrolyzed version of the Complete Gluten Mix, was found to be the most suitable, as it contained <50 kDa gluten peptides and gave similar absorbance readings to the majority of ELISA kit standards tested, and overlaid the GlutenTox® Competitive G12 antibody calibration curve, which was designed against the 33-mer immunogenic peptide from wheat. Additionally, no gluten bands were observed on the Wes for the enzymes of interest, which was confirmed through ELISA analysis.